Resepsi Masyarakat Pesisir Pantai Air Manis Kota Padang Terhadap Hadis dalam Tradisi Raba’akia” - Ibasrol, Ibasrol; Zulfikri, Zulfikri; Hakiim, Luqmanul (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2021)
This article is motivated by mysticism about the last Wednesday in the month of Safar which is believed by the people of Air Manis, Padang, West Sumatra, as the source of disaster. The community performs the raba'akia ritual to avoid the disaster. They believe it comes from the hadith of the Prophet about the arrival of a continuous plague on the last Wednesday of the month of Safar. This research is in the form of qualitative research using an ethnographic approach in the perspective of living hadith, also elaborating the theory of Coastal Islam which was initiated by Nursyam. This study aims to describe the raba'akia tradition as a result of the transmission of local culture into local Islamic culture originating from the hadith of the Prophet Muhammad. with the sociocultural context of the Air Manis community. This research finds that people are trying to articulate Islamic teachings about the hadith of the arrival of a disaster on the last Wednesday of the month of Safar. The raba'akia tradition is maintained by the Air Manis community because it has been commemorated from generation to generation by the Air Manis community. Every procession in the raba'akia ritual shows the existence of "self-purification" and "hoping for blessings" carried out by various means. One of the highlights is the use of aia paureh or holy water which is believed by the community to be able to provide blessings and resist disease and calamities that will befall the Air Manis Community